2005
DOI: 10.1038/sj.bmt.1705152
|View full text |Cite
|
Sign up to set email alerts
|

Early administration of recombinant erythropoietin improves hemoglobin recovery after reduced intensity conditioned allogeneic stem cell transplantation

Abstract: Summary:The use of recombinant human erythropoietin (rHuEPO) has been controversial after myeloablative allogeneic Stem cell transplantation (allo-SCT). Reduced intensity conditioning regimens (RIC) offer a novel approach that might translate into a different profile of erythropoietic recovery. We treated 20 consecutive patients with rHuEPO early after matched sibling RIC allo-SCT. Conditioning included fludarabine, busulfan and antithymocyte globulin. EPO treatment was analyzed in terms of toxicity, impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Comparison with our trial is difficult because they did not report on more standard response criteria (proportion of patients achieving Hb response or Hb correction), used a more intensive conditioning regimen, and provided systematic oral iron supplementation compared to more targeted intravenous iron supplementation in our trial. For patients receiving RBC transfusions, their use of rHuEPO was associated with a trend towards reduced requirements [37]. The same authors also previously showed that RBC transfusion needs after NMSCT correlated inversely with pretransplant Hb levels [36].…”
Section: Weeks After Nmsctmentioning
confidence: 71%
See 2 more Smart Citations
“…Comparison with our trial is difficult because they did not report on more standard response criteria (proportion of patients achieving Hb response or Hb correction), used a more intensive conditioning regimen, and provided systematic oral iron supplementation compared to more targeted intravenous iron supplementation in our trial. For patients receiving RBC transfusions, their use of rHuEPO was associated with a trend towards reduced requirements [37]. The same authors also previously showed that RBC transfusion needs after NMSCT correlated inversely with pretransplant Hb levels [36].…”
Section: Weeks After Nmsctmentioning
confidence: 71%
“…All these findings indicate that, after NMSCT, the pathophysiology of endogenous EPO production does not account for response to rHuEPO therapy. There is only a single other study investigating the impact of rHuEPO therapy starting on day 1 after NMSCT in 20 patients [37]. All of them, vs only 63% of controls, achieved an Hb level greater than 11 g/dL after a median of 30 days and 70% of them, vs only 19% of controls, maintained it in the second month.…”
Section: Weeks After Nmsctmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have also reported benefit for treatment with rHuEpo after allogeneic transplant. 78,79 Exploiting the same argument as in the autologous setting, Baron et al 80 showed that treatment with rHuEpo starting at day þ 30 or beyond, in patients transplanted with allogeneic peripheral blood stem cells, resulted in transfusion independence within 2 weeks in 12/13 patients versus 50% of patients in an historical control group. The mean Hb concentrations were significantly higher in the treatment compared to the control groups from day þ 60 post-transplant.…”
mentioning
confidence: 99%
“…17 Two recent studies have investigated the use of Epo after nonmyeloablative conditioning or RIC. 35,36 Ivanov et al 35 gave Epo (either 30 000 IU epoetin-beta or 150 mg darbepoetinealpha per week, started on day 1) to 20 consecutive patients following RIC allogeneic HCT (Epo group). Conditioning combined fludarabine, busulfan and ATG.…”
mentioning
confidence: 99%